Reading capital : the complete edition - Althusser, Louis; Balibar, Etienne; Fernbach, David (London ; New York : Verso, the imprint of New Left Books, 2015)
"A classic work of Marxist analysis, available unabridged for the first time Originally published in 1965, Reading Capital is a landmark of French thought and radical theory, which sought to reconstruct Western Marxism from its foundations. Previously only available in English in a highly abridged form, this 50th anniversary edition restores original chapters by Roger Establet, Pierre Macherey and Jacques Ranciere, accompanied by a major new introduction by Etienne Balibar on the book's continued impact. France's greatest philosophers scrutinize many of the most fundamental points in Marx's iconic text to reveal its philosophical core. From the Trade Paperback edition"--
"First published (abridged) in this English translation by New Left Books 1970. First Verso edition published 1997. Part Two first published in English in Economy and Society, 1976" -- title page verso.
boek
Keywords: Marx, Karl, -- 1818-1883.; Marxian economics; POLITICAL SCIENCE / History & Theory